3D graphics visualization for mobile user navigation - Ibrahim, Adamu Abubakar (Kulliyyah of Information and Communication Technoloy, International Islamic University Malaysia, 2012)
3D maps in mobile devices for navigation aid have been created to overcome the weaknesses of conventional 2D maps which require users to interpret its various symbols and legends. Now it has become possible to render large and detailed 3D map of cities in mobile devices at interactive rates over 5fps (frame rate per second) to 30fps. Mobile devices with low computing resources may also use manipulated photos in order to give the illusion of 3D presentation. Owing to this recent development, the concept of 3D representation in mobile devices for multi-users interactive navigation aid is proposed. It is aimed at helping people to navigate in unfamiliar locations. In today's world, mobility and communication have become essential. People may frequently find themselves asking: 'Where am I right now?', 'How do I get from X to Y?', and 'How can I tell Z?” The proposed system of 3D maps in mobile devices for navigation aid allows several mobile device users to view their own and the other users' locations at the same time, while being stationary or on-the-move. Voronoi diagram/Delaunay triangulation and A-star pathfinding are the algorithms for establishing user locations and their distances, apart from finding the shortest part from Location X to Y. A prototype of this system was developed to demonstrate the pros and cons of the practical application of this new concept. This research uses an observational research, field experiment, qualitative interview and quantitative survey to investigate navigation practices with 3D representation in mobile devices as a navigation aid. The research findings include discussion of the features of navigation practices with the aid of 3D representation in mobile devices and a critical assessment of the factors influencing its usage.